2020
DOI: 10.1029/2019wr025492
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying Geochemical Processes of Arsenic Mobility in Groundwater From an Inland Basin Using a Reactive Transport Model

Abstract: High arsenic (As) groundwater is frequently found in inland basins, yet the contributions of different processes to aqueous As distributions remain unresolved. In the Hetao Basin, a typical inland basin, groundwater As concentrations generally increased from the alluvial fan through the transition area to the flat plain. A geochemical process‐based reactive transport model was established to evaluate and quantify the processes of As mobilization in the northwestern Hetao Basin. Thirty‐six groundwater samples a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 92 publications
2
26
0
Order By: Relevance
“…Identifying a valid site‐specific conceptual model able to describe As mobility in groundwater is fundamental for many purposes related to As risk management. This includes the setup of process‐based geochemical models (e.g., Appelo & Postma, 2005; Gao et al, 2020; Jakobsen et al, 2018; Michael & Khan, 2016; Postma et al, 2007; Rathi et al, 2017; Rotiroti et al, 2014) predicting the spatial and temporal scales of occurrence of As concentrations in groundwater (e.g., predicting where As concentrations exceed the 10 μg/L recommended by World Health Organization [WHO]).…”
Section: Introductionmentioning
confidence: 99%
“…Identifying a valid site‐specific conceptual model able to describe As mobility in groundwater is fundamental for many purposes related to As risk management. This includes the setup of process‐based geochemical models (e.g., Appelo & Postma, 2005; Gao et al, 2020; Jakobsen et al, 2018; Michael & Khan, 2016; Postma et al, 2007; Rathi et al, 2017; Rotiroti et al, 2014) predicting the spatial and temporal scales of occurrence of As concentrations in groundwater (e.g., predicting where As concentrations exceed the 10 μg/L recommended by World Health Organization [WHO]).…”
Section: Introductionmentioning
confidence: 99%
“…According to Figure 8, the As concentration shows a tendency of a significant increase as the HCO3proportion increases, which indicates that As release is related to high HCO3concentrations. A significant correlation between As and HCO3 -has been observed in groundwater of the Ganges plain [41], Hetao Basin [42], and Guide Basin [22]. Studies suggested that the HCO3 -ion can substitute arsenate from the surface sites of iron oxides, leading to arsenic mobilization [43][44][45].…”
Section: Competitive Desorption Of Asmentioning
confidence: 99%
“…Natural contamination of groundwater by arsenic is a widespread problem in SE Asia ( van Geen et al, 2003 , Winkel et al, 2011 , Kocar et al, 2014 , Stahl et al, 2016 , Gao et al, 2020 ). Groundwater arsenic concentrations in the floodplains of SE Asia are the result of interacting hydrochemical, sedimentary and geological processes.…”
Section: Introductionmentioning
confidence: 99%
“…Groundwater arsenic concentrations in the floodplains of SE Asia are the result of interacting hydrochemical, sedimentary and geological processes. Arsenic is released to groundwater from iron hydroxides reduced by organic matter under anoxic conditions ( Postma et al, 2007 , Kocar et al, 2014 , Postma et al, 2016 , Gao et al, 2020 ). With time the reactivity of the organic matter in an aquifer decreases, and the rate of the reduction processes and the resulting groundwater arsenic content decreases ( Lawson et al, 2016 , Postma et al, 2016 , Jakobsen et al, 2018 ), also due to large water volumes recharged through the aquifer, leaching sorbed arsenic from the sediment ( Kocar et al, 2014 , Jakobsen et al, 2018 , Sø et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%